Elite futsal: sex-based differences in players' flexibility - Antonio Cejudo; Francisco Javier Robles-Palazón; Pilar Sainz de Baranda (Federación Extremeña de Balonmano; University of Extremadura, 2019)
The objective of the present study was to analyze the differences in muscle flexibility profile according to sex in elite futsal players. A total of 22 players (12 men, 10 women) were assessed using the basic version of the ROM-SPORT protocol following the recommendations established by the American Medical Association. A descriptive analysis of the values of the ten movements evaluated was performed. A t-test for independent samples was applied to observe the existence of significant differences between sexes. Statistical analysis found significant differences in the range of motion (ROM) of the internal rotation of the hip, the ROM of the external rotation of the hip, the ROM of the hip abduction, the ROM of abduction of the hip with it flexed, in the ROM of the hip extension and in the ROM of the knee flexion. Elite male futsal players have higher flexibility values than female players of the same sport and competitive level in the adductor, ilio-psoas and quadriceps muscles. By contrast, female futsal players have higher values in the rotator muscles of the hip.